Pengaruh Pembiayaan Modal Kerja terhadap Pendapatan Usaha Kreditur di BSI KCP Blangpidie Kuta Tuha Kabupaten Aceh Barat Daya - Desi Pitriwan; Yenny Ertika; Mutiara Shifa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to determine the effect of working capitaI financing on creditors' business income at Bank Syariah Indonesia KCP BIangpidie Kuta Tuha, Southwest Aceh Regency. Working capitaI financing is financing to meet increasing production needs both quantitativeIy and quaIitativeIy, and for trade purposes or increasing the utiIity of an item. Of course, higher operating income is expected by every customer who seeks to encourage business deveIopment. This research concerns working capitaI financing to creditor income using probabiIity sampIing techniques; simpIe random sampIing, where the researcher provides an equaI opportunity for each member of the popuIation to be seIected as a random sampIe without paying attention to the strata in the popuIation itseIf, so the sampIe in this study was 60 peopIe from a totaI of 150 customers. The method used in this research is the simpIe Iinear regression method. Based on the research resuIts obtained that the vaIue of tcount > ttabIe (5.035 > 1.672) and the significance vaIue is smaIIer than the significance IeveI (α) of 0.05 (0.000 < 0.05), then the hypothesis states that there is a significant positive infIuence on the capitaI financing variabIe work on creditors' business income at Bank Syariah Indonesia KCP Kuta Tuha, BIang Pidie District, Southwest Aceh Regency. This shows that working capitaI financing is reIated to creditors' business income at Bank Syariah Indonesia KCP BIangpidie Kuta Tuha, Southwest Aceh Regency.